2017
DOI: 10.1128/aac.00308-17
|View full text |Cite
|
Sign up to set email alerts
|

A Waterborne Outbreak of Shigella sonnei with Resistance to Azithromycin and Third-Generation Cephalosporins in China in 2015

Abstract: Here, we report for the first time a waterborne outbreak of Shigella sonnei in China in 2015. Eleven multidrug-resistant (MDR) S. sonnei isolates were recovered, showing high resistance to azithromycin and third-generation cephalosporins in particular, due to an mph(A)-and bla CTX-M-14 -harboring IncB/O/K/Z group transmissible plasmid of 104,285 kb in size. Our study highlights the potential prevalence of the MDR outbreak of S. sonnei in China and its further dissemination worldwide with the development of glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…IncI and IncB/O plasmids belong to the IncIcomplex (IncI, IncB/O, IncK, IncZ), which have comparable antisense RNA plasmid replication control mechanisms 12 . Our results concur with previous reports that proposed a commonality of IncI-complex plasmids associated with the bla CTX-M element in S. sonnei from countries at various stages of economic development 8,11,[13][14][15][16][17] . The sampling of these plasmids by cipR S. sonnei could be attributed to several factors, including the close genetic relatedness between Shigella and E. coli, the propensity of S. sonnei to acquire AMR plasmids, and the circulation of highly transmissible AMR plasmids in commensal E. coli.…”
supporting
confidence: 93%
“…IncI and IncB/O plasmids belong to the IncIcomplex (IncI, IncB/O, IncK, IncZ), which have comparable antisense RNA plasmid replication control mechanisms 12 . Our results concur with previous reports that proposed a commonality of IncI-complex plasmids associated with the bla CTX-M element in S. sonnei from countries at various stages of economic development 8,11,[13][14][15][16][17] . The sampling of these plasmids by cipR S. sonnei could be attributed to several factors, including the close genetic relatedness between Shigella and E. coli, the propensity of S. sonnei to acquire AMR plasmids, and the circulation of highly transmissible AMR plasmids in commensal E. coli.…”
supporting
confidence: 93%
“…The findings in this study associated the outbreak to multidrug-resistant Salmonella enterica serovar Typhi ingested through well water that served as the sole source of drinking water in the community, but was unacceptably polluted with dead and decaying bodies of animal, fecal material, and garbage. Similarly, Ma et al [ 287 ] reported the waterborne outbreak of shigellosis in China caused by Shigella sonnei with resistance to azithromycin, and third class cephalospsorins, due to mph (A) and bla CTX-M-14 -harboring IncB/O/K/Z group transmissible plasmid. In addition, Akoachere et al [ 288 ] unravelled the persistence of multidrug-resistant toxigenic Vibrio cholerae O1 in water samples (taps, dug wells, and streams) collected from New Bell—Doula, and associated these bacteria strains with the 2010–2011 cholera epidemic that recorded the highest number of death cases in the Littoral province of Cameroon.…”
Section: The Great Challenge: Antibiotics Resistancementioning
confidence: 99%
“…Strong [355,[580][581][582][583][584] Waterborne OI [284] Torovirus Toroviruses are enveloped viruses that have been linked to enteric infections in horses (Berne virus), cattle (Breda virus), pigs, and humans and transmission is thought to be via the faecal-oral route. In humans toroviruses have been found in infants with necrotising enterocolitis but their role in gastroenteritis remains unproved.…”
Section: Schistosoma Spindalementioning
confidence: 99%